2022
DOI: 10.1038/s41467-022-29442-x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase STUB1 destabilizes IFNγ-receptor complex to suppress tumor IFNγ signaling

Abstract: The cytokine IFNγ differentially impacts on tumors upon immune checkpoint blockade (ICB). Despite our understanding of downstream signaling events, less is known about regulation of its receptor (IFNγ-R1). With an unbiased genome-wide CRISPR/Cas9 screen for critical regulators of IFNγ-R1 cell surface abundance, we identify STUB1 as an E3 ubiquitin ligase for IFNγ-R1 in complex with its signal-relaying kinase JAK1. STUB1 mediates ubiquitination-dependent proteasomal degradation of IFNγ-R1/JAK1 complex through I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 78 publications
3
27
0
Order By: Relevance
“…These findings are further corroborated in humans where patients harboring loss-of-function mutations in STUB1 exhibited aging phenotypes . More recently, evidence suggests that STUB1 might play additional roles in regulating immunity. In accordance, we and others have shown that STUB1 constitutively constrains interferon-γ sensing by downregulating the interferon-γ cell surface receptor. As a result, inactivation of STUB1 inhibited the growth of cancer cell lines in vitro after prolonged treatment with interferon-γ and can facilitate the clearance of STUB1-deficient cells by cytotoxic T cells in a context-dependent mouse model . However, these studies exclusively deleted STUB1 in malignant cells, while leaving the gene unperturbed in the immune and stromal cells.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…These findings are further corroborated in humans where patients harboring loss-of-function mutations in STUB1 exhibited aging phenotypes . More recently, evidence suggests that STUB1 might play additional roles in regulating immunity. In accordance, we and others have shown that STUB1 constitutively constrains interferon-γ sensing by downregulating the interferon-γ cell surface receptor. As a result, inactivation of STUB1 inhibited the growth of cancer cell lines in vitro after prolonged treatment with interferon-γ and can facilitate the clearance of STUB1-deficient cells by cytotoxic T cells in a context-dependent mouse model . However, these studies exclusively deleted STUB1 in malignant cells, while leaving the gene unperturbed in the immune and stromal cells.…”
Section: Introductionsupporting
confidence: 53%
“…15−17 As a result, inactivation of STUB1 inhibited the growth of cancer cell lines in vitro after prolonged treatment with interferon-γ 17 and can facilitate the clearance of STUB1-deficient cells by cytotoxic T cells in a contextdependent mouse model. 16 However, these studies exclusively deleted STUB1 in malignant cells, while leaving the gene unperturbed in the immune and stromal cells. Since inhibition of STUB1 in these latter tissues may influence the therapeutic effect and on-target toxicities, finding a tool compound for STUB1 will pave the way for chemical genetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Here, using several murine and human cell lines, we provided multiple lines of evidence that STUB1 downregulates IFNGR1 to dampen IFNγ sensing. During preparation of this manuscript, Peeper and co-workers arrived at a similar conclusion where they elegantly identified STUB1 as www.nature.com/scientificreports/ with MS proteomics 53 . This independent finding further strengthens the case of STUB1 as an intracellular checkpoint and barrier for IFNγ sensing.…”
Section: Discussionmentioning
confidence: 74%
“…The linear ubiquitination at Lys652 was reported to inhibit STAT1 binding to the type-I interferon receptor IFNAR 26 and the ubiquitination at Lys249 mediated by STUB1 promoted JAK1 degradation. 27 Subsequent studies need to clarify whether these newly identified ubiquitination sites are capable of regulating signal transduction and whether they are specific to the SARS-CoV-2 infection process.
Fig.
…”
Section: Resultsmentioning
confidence: 99%